2021
DOI: 10.1111/dom.14527
|View full text |Cite
|
Sign up to set email alerts
|

Glucose control using fast‐acting insulin aspart in a real‐world setting: A 1‐year, two‐centre study in people with type 1 diabetes using continuous glucose monitoring

Abstract: Aim To evaluate the efficacy and safety of switching from traditional mealtime insulins to fast‐acting insulin aspart (Fiasp) in a “real‐world” clinical practice setting in adult people with type 1 diabetes (PWD1) who were using intermittently scanned or real‐time continuous glucose monitoring (isCGM or rtCGM, respectively). Materials and Methods Data from 438 adult PWD1 (60% men, age 44.6 ± 16.2 years, diabetes duration 21.5 ± 14.0 years, isCGM/rtCGM: 391/47, multiple daily injections/continuous subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…Similarly, we had a 12% decrease in TAR, also superior to what was found on both studies (3% [ 19 ] and 4.6% [ 20 ]). Nevertheless, A1c did not improve significantly, which is aligned with some [ 17 , 20 ], but not all studies [ 16 , 18 , 19 ]. Besides the fact that the study was carried out in a population with a reasonably good metabolic control (Table 1 ), comparing the average of A1c with the previous year of faster aspart’s introduction may have been a limitation.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similarly, we had a 12% decrease in TAR, also superior to what was found on both studies (3% [ 19 ] and 4.6% [ 20 ]). Nevertheless, A1c did not improve significantly, which is aligned with some [ 17 , 20 ], but not all studies [ 16 , 18 , 19 ]. Besides the fact that the study was carried out in a population with a reasonably good metabolic control (Table 1 ), comparing the average of A1c with the previous year of faster aspart’s introduction may have been a limitation.…”
Section: Discussionsupporting
confidence: 69%
“…Comparing with adults’ trials, the 11% increase in TIR observed in our study was considerably higher, 3.2% [ 19 ] and 4% [ 20 ]. Similarly, we had a 12% decrease in TAR, also superior to what was found on both studies (3% [ 19 ] and 4.6% [ 20 ]). Nevertheless, A1c did not improve significantly, which is aligned with some [ 17 , 20 ], but not all studies [ 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, CGM also showed similar beneficial effects in real-life conditions. 68,69 Although Fiasp was not associated with an overall increased risk of hypoglycaemia compared with Iasp, in ONSET 1, higher rates of early postmeal hypoglycaemia were noted, 59 illustrating the need for careful management of subjects prone to early postprandial hypoglycaemia, such as those with gastroparesis.…”
Section: Discussionmentioning
confidence: 98%
“…There are limited real-world studies with faster aspart [17,18,22]. One of these studies explored patient and physician perspectives regarding the use of faster aspart and highlighted the benefit of increased dosing flexibility with faster aspart compared with other…”
Section: Discussionmentioning
confidence: 99%